Guilt and its relation to decision-making among top-tier Taekwondo referees in Iraq - Younis, Asst.Prof.Dr. Walid Dhunoun; Dhunoun, Prof. Dr. Walid Ghanem; Saleh, Prof. Dr. Mahmoud Shukr; Ragab, Prof. Dr. Walid Khaled (Sulaimani Journal for Humanities, 2025)
The research problem stemmed from the lack of studies addressing guilt and its relationship to decision-making, as well as the seriousness of guilt among Taekwondo referees and its negative impact on their psychological state, potentially leading to anxiety that affects their ability to make appropriate decisions. Despite the emphasis placed on this by researchers in psychology, the current research attempts to explore guilt and its relationship to decision-making among Taekwondo referees in Iraq by answering the following question: Does guilt affect decision-making among Taekwondo referees in Iraq? The research aims to identify the degree of guilt experienced by Taekwondo referees in Iraq, as well as their decision-making abilities, and to uncover the relationship between guilt and decision-making among Taekwondo referees in Iraq. The researchers used the descriptive method due to its suitability to the nature of the research. The research population consisted of Taekwondo referees in Iraq registered with the Iraqi Central Taekwondo Federation for the year (2024-2025), totaling (66) referees. International, first, and second division referees from all Iraqi governorates were selected purposively. The Guilt Scale for Football Referees, developed by Mohammed Yousef Hajjaj and Khaled Abdul Aziz (2022), was used. It consists of 36 items distributed across three axes: (Axis 1: Guilt towards violating ethics, rules, and laws of the game) consisting of 6 items; (Axis 2: Guilt towards others) consisting of 13 items; and (Axis 3: Guilt towards technical situations and errors) consisting of 27 items. The scale was adapted to be suitable for Taekwondo referees. The Decision-Making Scale, developed by Yousef Saleh Dhiab (2018) consisting of 20 items, was also used. Scientific analyses were performed on both research instruments, and the percentage, arithmetic mean, standard deviation, and simple correlation coefficient were used to statistically analyze the data. After presenting and discussing the results, the researchers concluded that the degree of guilt Guilt among Taekwondo referees is high, indicating that Taekwondo referees felt guilty. Taekwondo referees also feel guilty about technical situations and mistakes to a high degree, and no correlation was found between the guilt scale and the decision-making scale.
Keywords: Guilt; Taekwondo Referees; Decision Making